(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article describes Langston Hughes, a brilliant writer in American literature. And it includes facts about the poet's life path and role in literature. Langston Hughes (1901–1967) was a poet, social activist, novelist, playwright, columnist, and a significant figure of the Harlem Renaissance. Born in Joplin, Missouri, Hughes was the descendant of enslaved African American women and white slave owners in Kentucky.